Effect of Farmer Group Empowerment and Agribusiness Training Program on Productivity and Income of Coffee Farmers in West Java - Ayesha, Ivonne; Harahap, Gustami; Cahya, Darmawan Listya (West Science Interdisciplinary Studies, 2024)
This study investigates the impact of Farmer Group Empowerment and Agribusiness Training Programs on the Productivity and Income of coffee farmers in West Java. The research utilizes a quantitative approach with a sample of 200 coffee farmers and significantly positively affect ploys Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze the relationships between the key variables. The results indicate that both Farmer Group Empowerment and Agribusiness Training Programs significantly positively affect Productivity and Income. However, Farmer Group Empowerment shows a stronger impact on productivity compared to training programs, emphasizing the importance of collective action in enhancing farming practices. These findings highlight the need for an integrated approach to agricultural development, combining empowerment with technical training to ensure sustainable improvements in farmers' livelihoods. The study provides valuable insights for policymakers and agricultural development practitioners seeking to promote rural development and increase smallholder farmers' productivity and income.